Effect of chitosan quaternary ammonium salt on the growth and microcystins release of Microcystis aeruginosa. Issue 84 (26th August 2016) - Zhu, Yaowen; Pei, Haiyan; Hu, Wenrong; Jin, Yan; Xu, Hangzhou; Ren, Ying; Xue, Di
Abstract : This present study was the first time to research the application potential of HTCC in M. aeruginosa control. To balance the inhibition efficiency of M. aeruginosa and the release of MCs, 1.2 mg L −1 was chosen as appropriate dose. Abstract : Developing effective methods to control Microcystis aeruginosa ( M. aeruginosa ) bloom is significant for repelling the adverse impact from hepatotoxic microcystins (MCs). Chitosan quaternary ammonium salt (HTCC), a water-soluble derivative of chitosan, shows excellent antioxidant and antibacterial properties. The present study was the first to research the application potential of HTCC in M. aeruginosa control. Five experimental groups with different doses of HTCC (0, 0.6 mg L −1, 1.2 mg L −1, 2.4 mg L −1, and 4.8 mg L −1 ) were built to explore the effects of HTCC on the growth and physiological changes of M. aeruginosa and the release of intracellular matter. The results indicated that the growth of M. aeruginosa was effectively inhibited by HTCC, and the inhibition efficiency was dependent on dosage within 7 days (d). Especially for the treatment with 4.8 mg L −1 HTCC, the inhibitory rate remained above 93.6% after 7 d exposure. However, the integrity of M. aeruginosa cells treated with 2.4 and 4.8 mg L −1 HTCC may be damaged and partial MCs were released. Furthermore, the release of MCs in the 1.2 mg L −1 HTCC treated groups was significantly lower than that of the control sample. To balance the inhibition efficiency of M. aeruginosa and the release of MCs, 1.2 mg L −1 was chosen as the appropriate dose for inhibiting the growth of M. aeruginosa and reducing the release of MCs. HTCC could damage the antioxidant defense system of M. aeruginosa and exhibit the inhibitive property. The results demonstrated HTCC can be used as an effective and safe inhibitor to control algal blooms.